Model Pemberdayaan Masyarakat Pesisir melalui Inovasi Kewirausahaan Digital dan Sistem Informasi Potensi Lokal - Hidayat, Andi Ircham; Rasdi; Asbara, Nurkhalik Wahdanial; Kulsaputro, Januar (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program was carried out in Tekolabbua Village, Pangkep Regency, with the primary objective of exploring and mapping local potentials through digital entrepreneurship innovation and the development of a local potential information system. The program responds to the lack of structured documentation of local resources and limited digital competence among coastal communities. The approach includes participatory mapping, digital training, community organizing, and system development. The results show the creation of a digital-based local potential mapping platform, improved community understanding of local assets, and increased digital skills among participants. This model supports evidence-based planning and strengthens socio-economic resilience in coastal areas.